Preconception Care Recommendations, Training, and Competency of Primary Healthcare Nurses in South Africa: A Quantitative Descriptive Study - Winifred Chinyere Ukoha RN, MSc, PhD; Ntombifikile Gloria Mtshali RN, MSc, PhD (SAGE Publishing, 2023)
Introduction There has been a growing interest in preconception care (PCC) as a primary means of tackling the high maternal and child mortality rates, as evidence has shown that the state of maternal health before conception can have a direct impact on the health of the mother and baby. Primary care nurses have been recognized as the highest providers of sexual and reproductive healthcare to the vulnerable population in resource-constrained settings. Objective This study aimed to examine and describe the PCC recommendations, training, and competency of primary healthcare (PHC) nurses in South Africa. Methods A cross-sectional descriptive study was conducted among 196 PHC nurses to examine the PCC recommendations, training, and competency. A self-administered survey tool was used for data collection. Results The self-reported PCC recommendations, training, and competency of PHC nurses were 63.3%, 88.3%, and 94.9%, respectively, in each aspect. The PCC training among the respondents was mainly in-service training. The only training that was indicated to have been done primarily at a pre-service level was training about reproductive life plan screening and brief counseling. Over 20% of the respondents indicated that they did not receive any training on how to provide alcohol, drug, or tobacco cessation services and how to conduct preconception risk assessments. Conclusion Although PHC nurses reported a high level of recommendation, training, and competency, their level of reported PCC practice is not equivalent to their provision, as they rendered PCC services to fewer women, and they also reported fewer women seeking PCC. A future longitudinal study is required to examine the reason for low PCC-seeking habits among those at high risk of adverse pregnancy outcomes and contextual factors influencing the provision of PCC services among healthcare workers.